2012
DOI: 10.4028/www.scientific.net/amr.506.226
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Polycaprolactone/Ethanolic Extract Propolis Nanofibers Films

Abstract: Recent years, propolis has plenty of biological and pharmacological properties and its mechanisms of action have been widely investigated. There is a substantive database on the biological activity and toxicity of propolis indicating it may have many antibiotic, antifungal, antiviral and antitumor properties, among other attributes. The one-step incorporation of propolis into nanofibrous mats of polycaprolactone (PCL) by electrospinning was demonstrated. In this research, the preparation of the PCL nanofibers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Sutjarittangtham et al showed that fiber diameters were decreased by the addition of different concentration of Ps. The fiber diameters were decreased from 140-190 nm to 60-70 nm due to higher Ps content [58]. It is also important to mention that when analyzing the surfaces of the strands there are no cracks or defects (such as, especially, micropores in the structure of strands or shrinking of the strands) which could affect the structural integrity, especially when exposed to tensile loading.…”
Section: Scanning Electron Microscopy (Sem)mentioning
confidence: 99%
“…Sutjarittangtham et al showed that fiber diameters were decreased by the addition of different concentration of Ps. The fiber diameters were decreased from 140-190 nm to 60-70 nm due to higher Ps content [58]. It is also important to mention that when analyzing the surfaces of the strands there are no cracks or defects (such as, especially, micropores in the structure of strands or shrinking of the strands) which could affect the structural integrity, especially when exposed to tensile loading.…”
Section: Scanning Electron Microscopy (Sem)mentioning
confidence: 99%
“…The results indicated that blending propolis with polyurethane led to improved physiochemical and biological characteristics. Similar studies on propolis nanofibers preparation were also reported, but using different polymers such as polyvinyl alcohol [ 92 , 93 ], polycaprolactone [ 94 ], and poly(lactide-co-glycolide) [ 95 ].…”
Section: Current Nanoformulations Of Propolismentioning
confidence: 78%
“…The potential of electrospun PCL for wound healing and skin tissue engineering has recently been comprehensively reviewed, 3 encompassing blending or coating with natural macromolecules such as collagen, gelatin or chitosan, 20 or the incorporation of natural antimicrobials such as curcumin, shikonin or Inula graveolens (L.) 3,21 . PCL has previously been electrospun with ethanolic extract propolis (EEP), 22 in a study that considered the effect of the EEP concentration with respect to fixed electrospinning parameters. Propolis extract from different geographical sources has also been incorporated in other electrospun polymer systems, including polyurethane, polyvinylpyrrolidone (PVP), poly vinyl (alcohol) (PVA), zein and poly(lactide‐co‐glycolide) copolymer (PLGA) 3,23–25 .…”
Section: Introductionmentioning
confidence: 99%